Lateral soft‐tissue structures contribute to cruciate‐retaining total knee arthroplasty stability. Issue 9 (21st November 2016) - Athwal, Kiron K.; El Daou, Hadi; Lord, Breck; Davies, Andrew J.; Manning, William; Rodriguez y Baena, Ferdinando; Deehan, David J.; Amis, Andrew A.
ABSTRACT: Little information is available to surgeons regarding how the lateral structures prevent instability in the replaced knee. The aim of this study was to quantify the lateral soft‐tissue contributions to stability following cruciate‐retaining total knee arthroplasty (CR TKA). Nine cadaveric knees were tested in a robotic system at full extension, 30°, 60°, and 90° flexion angles. In both native and CR implanted states, ±90 N anterior–posterior force, ±8 Nm varus–valgus, and ±5 Nm internal–external torque were applied. The anterolateral structures (ALS, including the iliotibial band), the lateral collateral ligament (LCL), the popliteus tendon complex (Pop T), and the posterior cruciate ligament (PCL) were transected and their relative contributions to stabilizing the applied loads were quantified. The LCL was found to be the primary restraint to varus laxity (an average 56% across all flexion angles), and was significant in internal–external rotational stability (28% and 26%, respectively) and anterior drawer (16%). The ALS restrained 25% of internal rotation, while the PCL was significant in posterior drawer only at 60° and 90° flexion. The Pop T was not found to be significant in any tests. Therefore, the LCL was confirmed as the major lateral structure in CR TKA stability throughout the arc of flexion and deficiency could present a complex rotational laxity that cannot be overcome by the other passive lateral structures or the PCL. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1902–1909, 2017.